Persepsi Mahasiswa Tentang Institutional Repository dalam Memenuhi Kebutuhan Informasi di Unversitas Islam Negeri Syekh Ali Hasan Ahmad Addary - Pohan, Samia; Sayekti, Retno; Faturrahman, Muslih (TSAQOFAH, 2023)
The purpose of this study is to analyze the students perceive about how the Institutional Repository is fulfilling the information needs at the Unversitas Islam Negeri Syekh Ali Hasan Ahmad Addary. The research design used is qualitative with the descriptive research method. In collecting the data, the researcher used interviews, observation, and documentation, then analyzed descriptively. This research uses purposive sampling technique in selecting informants. In analyzing the data, the researcher used three methods, the data reduction, the display data, and making conclusion. From the results of the study, it can be seen that students' perceptions of the Institutional Repository led to positive perceptions in terms of attitudes, feelings, knowledge and expectations. Although sometimes there are various obstacles when looking for information using the repository. Students hope that the repository will provide the better information services for the future.